2019
DOI: 10.1111/jocs.14303
|View full text |Cite
|
Sign up to set email alerts
|

Preventing spasm of the radial artery conduit during coronary artery bypass grafting: Nicardipine versus verapamil

Abstract: Background and aim of the study: In vitro studies have shown a reduction in radial artery spasm with the use of calcium antagonists. The purpose of this study was to evaluate the efficacy of topical treatment of the radial artery conduit using either verapamil or nicardipine before the anastomoses.Methods: This prospective randomized study included 131 patients, who underwent coronary artery bypass grafting surgery with the use of the radial artery as a conduit. In 65 patients, the harvested radial artery was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Our investigation aimed to compare the proximal and distal ends of the RA regarding the histopathological characteristics. Previous studies have shown that the rate of RA vasospasm during CABG varies between 0.3 and 10 % [ 2 , 5 , 10 ]. Comparably, we found the RA vasospasm to be 1.41 %.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our investigation aimed to compare the proximal and distal ends of the RA regarding the histopathological characteristics. Previous studies have shown that the rate of RA vasospasm during CABG varies between 0.3 and 10 % [ 2 , 5 , 10 ]. Comparably, we found the RA vasospasm to be 1.41 %.…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro study, which was done on 74 RA segments and 85 internal thoracic artery segments, it was shown that using Nicardipine and Nitroglycerine cocktail exhibited the best relaxant results [ 7 ]. In a randomized control trial on 131 subjects who underwent CABG with RA as a graft, the arterial flow was compared after using Verapamil versus Nicardipine, and it was concluded that the administration of topical Nicardipine was safe and effective [ 10 ]. A narrative review by Guo-Wei He et al showed that using a combination of a calcium channel blocker and a topical nitric oxide (NO)-releasing agent such as TNG with liberal use of systemic calcium antagonist showed yielded favorable outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there is a decrease in arterial pressure and a loss of pulse in the radial artery. A radial arteriogram is therefore obtained in order to confirm radial artery spasm and correspondingly omit vessel injury 3 . It is crucial to perform angiography because pain may occasionally not be caused by a spasm but rather by coiling or looping in the radial, subclavian, or brachial arteries, which makes it difficult to move the catheter and the patient feels pain.…”
Section: Introductionmentioning
confidence: 99%